(1083) The Development of Economic Policy in the in the German Democratic Republic تطوير السياسة الاقتصادية في جمهورية ألمانيا الديمقراطية - Siegfried Voigtsberger; Werner Wubserlich. (INP., 2020)
In the immediate aftermath of World War II, Germany—particularly its eastern region—faced a severe economic and social crisis. The war had left nearly half of the industrial base destroyed, and infrastructure such as electricity production and rail transport was critically damaged. Housing in urban areas suffered extensive destruction, and the labor force was significantly diminished. Despite determined reconstruction efforts, the economic output in 1946 remained drastically below pre-war levels, highlighting the lasting impact of the fascist war on the nation's productive capacity.